Sub‐assembly experiments to determine PWM supply‐induced losses in electric machines. Issue 17 (26th April 2019) - Godbehere, Jonathan; Hopkins, Andrew; Drury, David; Mellor, Phil
Abstract : This paper presents a low‐cost approach to experimentally characterise the effect of the inverter supply on the losses in an electrical machine. The set‐up comprises of representative subassemblies of the stator and winding, referred to as 'motorettes', and a single phase, fast switching silicon‐carbide‐based converter. The sub‐assembly‐based thermal analysis has been shown to be a time and cost‐effective method to examine winding loss, over a range of operating conditions. In addition to the slot to stator thermal resistance and capacitance. This provides critical information for thermal model calibration and produces more accurate thermal and loss predictions of the full machine behaviour. A test arrangement has been devised to replicate the magnetic excitation of the electrical machine stator during normal operation. This builds upon previous techniques, to allow iron loss to be investigated. Through multiple tests using DC, AC, and PWM‐AC supplies, a 20% increase in iron loss is observed due to PWM effects.